Basal hippopotamines from the upper Miocene of Chorora, Ethiopia. Issue 3 (4th May 2017) - Boisserie, Jean-Renaud; Suwa, Gen; Asfaw, Berhane; Lihoreau, Fabrice; Bernor, Raymond L.; Katoh, Shigehiro; Beyene, Yonas
ABSTRACT: The Hippopotamidae have been a major component of the African wetland fauna for the last 7 million years, following the 'Hippopotamine Event, ' i.e., the sudden emergence in the fossil record of the subfamily Hippopotaminae, including both extant species. The general dearth of African fossiliferous deposits dated between 9.5 Ma and 7.5 Ma concealed until now the evolution that led to the Hippopotamine Event and the subsequent success of these large semiaquatic herbivores. Part of this evolution is unveiled by the hippopotamid dental remains found at Chorora, a late Miocene site of the southern Afar Depression in Ethiopia spanning most of the fossil-depleted time interval. Although fragmentary, these remains represent a new, mid-sized hippopotamid species dated to ca. 8 Ma, as well as a somewhat younger, larger form. A cladistic analysis of a large array of cetartiodactyls indicates that the Chorora taxa were basal to the latest Miocene hippopotamines. The new species displays a mosaic of dental characters that support the attribution of the new species to a new genus within Hippopotaminae. The new fossils also clarify the course of early hippopotamine dental evolution. The Chorora hippopotamids suggest that transition to a marked abundance of hippopotamines with their unique dental pattern in African ecosystems occurred within a relatively short time interval, most probably between 8 Ma and 7.5 Ma. http://zoobank.org/urn:lsid:zoobank.org:pub:47B9381F-E3B5-40C9-B9AB-51CC3D0D3A8A SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Boisserie, J.-R., G. Suwa, B. Asfaw, F. Lihoreau, R. L. Bernor, S. Katoh, and Y. Beyene. 2017. Basal hippopotamines from the upper Miocene of Chorora, Ethiopia. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1297718.